The Point of Coincidence and Common Fixed Point for Three Mappings in Cone Metric Spaces - Anil Kumar; Savita Rathee; Navin Kumar (Journal of Applied Mathematics)
The aim of this paper is to present the point of coincidence and common fixed point for three mappings in cone metric spaces over normal cone which satisfy a different contractive condition. Our result generalizes the recent related results proved by Stojan Radenović (2009) and Rangamma and Prudhvi (2012).